2020
DOI: 10.1016/j.nlm.2019.107132
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of intrinsic excitability as a function of learning within the fear conditioning circuit

Abstract: Experience-dependent neuronal plasticity is a fundamental substrate of learning and memory. Intrinsic excitability is a form of neuronal plasticity that can be altered by learning and indicates the pattern of neuronal responding to external stimuli (e.g. a learning or synaptic event). Associative fear conditioning is one form of learning that alters intrinsic excitability, reflecting an experience-dependent change in neuronal function. After fear conditioning, intrinsic excitability changes are evident in brai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 196 publications
(287 reference statements)
0
6
0
Order By: Relevance
“…Along with the amygdala, hippocampus and prefrontal cortex, the RSC, posterior cingulate cortex (PCC) and precuneus (PCu) have been implicated in emotional (particularly fear) learning and memory in both preclinical ( Todd et al, 2019 ; Vogt, 2019 ; Yousuf et al, 2020 ) and clinical ( Holschneider et al, 2014 ; Kveraga et al, 2015 ; Van den Stock et al, 2014 ; Zhan et al, 2018 ) studies. For instance, fear induction with exposure to video clips elicited higher activity in bilateral anterior insula and right hemispheric parahippocampal gyrus (PHG), PCC, and PCu ( Zhan et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Along with the amygdala, hippocampus and prefrontal cortex, the RSC, posterior cingulate cortex (PCC) and precuneus (PCu) have been implicated in emotional (particularly fear) learning and memory in both preclinical ( Todd et al, 2019 ; Vogt, 2019 ; Yousuf et al, 2020 ) and clinical ( Holschneider et al, 2014 ; Kveraga et al, 2015 ; Van den Stock et al, 2014 ; Zhan et al, 2018 ) studies. For instance, fear induction with exposure to video clips elicited higher activity in bilateral anterior insula and right hemispheric parahippocampal gyrus (PHG), PCC, and PCu ( Zhan et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Mechanisms of persistent activity in the fear circuit are intensively studied 64 . Understanding the cellular bases of the post-stress shift in PVT/CR+ activity requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…5 ). We focused on BS LIV鈥揤I aIC-BLA projecting neurons since bursting has been implicated in coincidence detection by deep-layer neurons ( Boudewijns et al, 2013 ; Shai et al, 2015 ), as well as the encoding of novelty and valence relating to different modalities ( Song et al, 2015 ; Dunn et al, 2018 ; Yousuf et al, 2019 ). Our PCA of intrinsic properties in BS LVI-VI aIC-BLA projecting neurons demonstrated that distinct plasticity rules are at play depending on the balance between the probability for associative learning and the certainty with which taste predicts the valence of experience during retrieval (Extended Data Figs.…”
Section: Discussionmentioning
confidence: 99%